Similarity and dissimilarity of conjugate relationships of Pi magnetic pulsations observed during excellent similar auroras - Sakurai, Tohru; Kadokura, Akira; Sato, Natsuo; Tonegawa, Yutaka (National Institute of Polar Research, 2006)
P(論文) Similarity and dissimilarity of conjugate relationships of Pi magnetic pulsations observed during excellent similar auroras at the conjugate stations, Tjornes in Iceland and Syowa Station in Antarctica are examined. The study revealed that characteristic Pi pulsations, Pi 2 pulsations and impulsive Pi 1 pulsations were prominently observed with a close relationship to aurora activities. During the substorm growth phase they showed a good similarity between the conjugate stations. How ever, at the onset of substorm expansion, the appearance of Pi pulsations showed prominent dissimilarity between the conjugate stations, suggesting that there might be some asymmetry of the ionosphere and magnetosphere conditions in between the northern and the southern hemispheres. departmental bulletin paper